Kemurungan dalam kalangan pesakit Kegagalan renal peringkat akhir (ESRF) yang menerima rawatan hemodialisis dl Kelantan - Yusof, Mahyuzy
Introduction: Individuals with ESRF face a variety of chronic recurrent stressors and significant lifestyle disruption. Thus, depression is common, but often underdiagnosed among this population. Objective: To study the prevalence of depression, physician-diagnosed depression among ESRF with hemodialysis. Researchers also assessed the association of depression with sociodemographic profiles, length of hemodialysis, comorbidities and 2 blood parameters which are level of serum albumin and hemoglobin. Methodology: This was a cross-sectional study. Sample was represented by 74 hemodialysis patient selected from 4 dialysis centres around Kelantan. Depression was measured by the standard Beck Depression Inventory (BDI-SF) with score of 0-63. Score ~ 14 indicated presence of depression. Result: Forty- six percent (46%) of the subjects had a BDI score ~14. Depression was found statistically significant with unemployed (p=O.OOOI), low level of education (p=0.033), low financial status (p=0.014) and poor social support (p=<O.OOOI). Interestingly, this study also found BDI scores seem to agree with Coping Model (Honeytnoon, Disenchantment, Discouragement and Long Term Adaptation). Depression significantly reaches high level during the first 2 years after initiation of dialysis and after five years of treatment. However, this study found no statistically significant in the association of depression and level of serum albumin and hemoglobin. Conclusion: The data suggest that the prevalence of depression is high but likely underdiagnosed and undertreated among hemodialysis patients. BDI is a short andsimple questionnaire that can help identify ESRF and hemodialysis patients with depression.